Analysis of the decrease of center pivot sprinkling system uniformity and its impact on maize yield - Lianhao, Li; Xinyue, Zhang; Xiaodong, Qiao; Guiming, Liu (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Early studies showed that the irregular operations of the center pivot sprinkling system would decrease its uniformity while the reason was lack of discussion. Taking Herman-Hein uniformity coefficient (CUH) and Distribution uniformity coefficient (DU) as evaluation indicators, the reason that irregular operation management and configurations can decrease the uniformity of center pivot sprinkling irrigation was discussed and the impact on maize yield was tested. The reasons for such decrease in uniformity include: (1) With the increase of moving speed, the effect of sprinkling overlaying became worse, which resulted in the lower uniformity of sprinkling irrigation; (2) With the increase of head pressure, the inlet pressure could be adjusted to the same pressure by pressure regulator, which kept the uniformity of sprinkling irrigation constant; (3) When end gun worked abnormally, total head pressure decreased, which led to the decrease of sprinkling irrigation’s uniformity; (4) When pressure regulator worked abnormally, the water flow was subject to great pressure loss, which could decrease the uniformity of sprinkling irrigation; (5) When pressure regulator was uninstalled, significant abnormality of sprinkling irrigation depth occurred, resulting in the decreasing of sprinkling irrigation’s uniformity; (6) Different types of nozzles could produce different uniformity of sprinkling irrigation, which was due to different structures of micro-nozzles; (7) Due to lower uniformity, at the seedling stage of maize, both height and seedling emergence rate decreased. Final yield decreased by 18.35%. This study is important to the proper use and the improvement of configuration selection and field management of center pivot sprinkling system.Keywords: center-pivot sprinkling system, uniformity, maize, yieldDOI: 10.3965/j.ijabe.20160904.1129Citation: Li L H, Zhang X Y, Qiao X D, Liu G M. Analysis of the decrease of center pivot sprinkling system uniformity and its impact on maize yield. Int J Agric & Biol Eng, 2016; 9(4): 108-119.